2018
DOI: 10.1038/s41413-018-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of latent transforming growth factor-β initiates the onset of temporomandibular joint osteoarthritis

Abstract: There is currently no effective medical treatment for temporomandibular joint osteoarthritis (TMJ-OA) due to a limited understanding of its pathogenesis. This study was undertaken to investigate the key role of transforming growth factor-β (TGF-β) signalling in the cartilage and subchondral bone of the TMJ using a temporomandibular joint disorder (TMD) rat model, an ageing mouse model and a Camurati–Engelmann disease (CED) mouse model. In the three animal models, the subchondral bone phenotypes in the mandibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Temporomandibular joint samples were harvested at indicated times and scanned using a microCT scanner (μCT50; SCANO, Switzerland) at a voltage of 50 kVp, a current of 200 µA and a resolution of 3.0 µm per pixel. The images were reconstructed and performed three‐dimensional histomorphometry based on a previous report . Briefly, two cubic regions of interest (each 100 × 100 × 100 µm 3 ) were defined from the middle of the centre and posterior third of the condylar subchondral cancellous bone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporomandibular joint samples were harvested at indicated times and scanned using a microCT scanner (μCT50; SCANO, Switzerland) at a voltage of 50 kVp, a current of 200 µA and a resolution of 3.0 µm per pixel. The images were reconstructed and performed three‐dimensional histomorphometry based on a previous report . Briefly, two cubic regions of interest (each 100 × 100 × 100 µm 3 ) were defined from the middle of the centre and posterior third of the condylar subchondral cancellous bone.…”
Section: Methodsmentioning
confidence: 99%
“…In the mandibular condylar cartilage, ageing causes reduction in chondrocytes number and viability, decrease in matrix synthesis, and the appearance of OA lesions along the articular surface of the joint . In the subchondral bone region, ageing animals exhibited significantly reduced bone volume …”
Section: Introductionmentioning
confidence: 99%
“…In the early stages of TMJ OA, upregulation of genes involved in osteoclast activity and/or an increase in RANKL/OPG ratio in subchondral bone contributes to an increase in subchondral bone turnover in biglycan/fibromodulin-deficient mice [53]. Osteoblast-specific transforming growth factor (TGF) -β1 transgenic mice in the bone marrow were used to have high levels of active TGF-β1 to assess the effect of overexpressed TGF-β1 on TMJ OA [54]. Through this model, excessive apoptosis of the mandibular chondrocytes, upregulation of MMP-9, MMP-13 and vascular endothelial growth factor (VEGF) in chondrocytes, and decreased bone mineral density were observed.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Under the circumstance, a novel therapeutic strategy in light of the recently emerging coupling mechanism of bone resorption and formation (Cao, 2011;Wan et al, 2012;Zhen and Cao, 2014;Sims and Martin, 2015;Xie et al, 2016) would be an ideal approach to treat subchondral bone as a target in OA. Many research findings have shown that TGF-β1 and IGF-1 in the bone matrix function to couple bone resorption and formation, and modulation of their activities can be an effective prevention and treatment for OA (Zhen et al, 2013;Xu et al, 2015;Cui et al, 2016;Zheng et al, 2018). Likewise, activity modulations of RANKL and Sema4D in other two cellular communications can also regulate bone resorption and formation.…”
Section: Regulatory Balance Between Bone Resorption and Formationmentioning
confidence: 99%